Inspiring citizen science innovation for sustainable development goal 6 in water quality monitoring in China - Wu, Yaqian; Washbourne, Carla; Haklay, Muki (Frontiers in Environmental Science, 2023)
Introduction: The global challenge of sustainable development is encapsulated in the 17 United Nations Sustainable Development Goals (SDGs), to which China is committed. As outlined in the UNESCO World Water Assessment Program (WWAP) report, water fundamentally impacts on sustainable development, making the achievement of SDG 6 (water and sanitation) crucial. China, as a leading manufacturing hub with extensive agriculture, grapples with challenges in monitoring SDG 6 indicators, especially concerning water quality. Methods: In light of these challenges, this study explores the utilisation of non-traditional data sources, specifically citizen science (CS), to address aspects of SDG 6 monitoring pertaining to water quality monitoring in China. Specifically, our study employs a combination of research techniques–including a literature review, semi-structured interviews, and participant observation–to critically evaluate 13 existing CS projects focused on water quality monitoring. A modified CS assessment framework has been utilised, offering a comprehensive, structured approach to evaluation. Results: In total, this analysis identified four key findings: 1) CS projects related to water monitoring in China predominantly focus on freshwater and drinking water; 2) Greater attention and support are needed for freshwater monitoring initiatives to align with China’s “ecological civilisation” policy; 3) Replacing “citizen science” with “public participation” may promote broader acceptance of these initiatives; 4) Training requires enhancement, particularly for participants from third- and fourth-tier cities as well as remote rural areas. Discussion: This research delineates feasible strategies for the future expansion and integration of CS projects throughout the country. It advocates for a more participatory data-driven approach to sustainable water management in China, given the highlighted challenges and the potential solutions unearthed through the use of citizen science and public participation.